Kajian Minimum Inhibitor Concentration (MIC) dan Minimum Bactericidal Concentration (MBC) Ekstrak Kulit Terong Ungu (Solanum melongena L) Sebagai Pengembangan Antibakteri Herbal - Wahyuni, Sri; Patang, Patang; Putra, Reski Praja (Jurnal Pendidikan Teknologi Pertanian, 2023)
Purple eggplant skin contains flavonoid which are antibacterial compounds, but mostly just becomes waste, even though purple eggplant skin extract has potential to be developed as herbal antibacterial. The purpose was to examine antibacterial activity, Minimum Inhibitor Concentration, and Minimum Bactericidal Concentration purple eggplant skin extract against pathogenic bacteria. Purple eggplant skin is extracted using the maceration method with 70% ethanol. The antibacterial activity test of purple eggplant skin extract was carried out by the method of diffusion using disc paper. Determination of MIC and MBC is carried out by a dense dilution method in a pour plate, with concentrations used 0%, 1.56%, 3.13%, 6.25%, 12.5%, 25%, 50%, and 100%. The results of measuring the diameter of the inhibitory zone are Staphylococcus aureus (7.4 mm), Bacillus cereus (8.8 mm), Salmonella sp. (7.0 mm), Escherichia coli (1.7 mm). These results showed purple eggplant skin extract had a good ability to inhibit pathogenic bacteria, except E. coli (weak inhibitory power). MIC value of eggplant skin purple extract was obtained at 12.5% in each test bacteria. At this concentration, the number of colonies was able to be reduced to 1 Colony log/mL in all three test bacteria. MBC value of eggplant skin purple extract was obtained at 50%, at this concentration, no bacterial growth was found in the three test bacteria.